KOLONISASI FUNGI PADA PROSES DEKOMPOSISI SERASAH DAUN Rhizophora mucronata BERDASARKAN TINGKAT SALINITAS DI KECAMATAN HAMPARAN PERAK KABUPATEN DELI SERDANG - Nafi Sakila; Yunasfi Djayus; Ani Suryanti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
R. mucronata is the dominan type of mangrove that grown in Hamparan Perak district. Mangrove’s litter that fall into the forest floor will be decomposed therefore it is involved the microorganism role such as fungi to produce nutrient in the waters. Fungi are the main decomposers in the decomposition of mangrove leaves. The purpose of this research is to know the population and the frequency of fungi colonization, hence to examine the number of species and index of fungi diversity in R. mucronata leaf litter at various levels of salinity. This research was conducted in February – June 2017. Purposive sampling is done by determine the 3 point observation station based on salinity difference. The results of this study show that the highest fungi population is at station 2 with salinity level 9 – 16 ppt ie 30,50 × 102 cfu / ml. The frequency of fungi colonization on the highest litter decomposition process is the type of Aspergillus. The highest number of fungi species is salinity level 1 – 8 ppt as many as 14 types of fungi. The diversity index of fungi type in Hamparan Perak district indicates the same range that is moderate which is describes adequate productivity, balance ecosystem and ecological pressure.Keywords: Mangrove, Leaf Litter, Rhizophora mucronata, Decomposition, Fungi, Nutrient of aquatic, Hamparan Perak District